H2 influenza viruses: designing vaccines against future H2 pandemics. (15th January 2019) - Reneer, Z. Beau; Ross, Ted M.
Abstract : Influenza-related pathologies affect millions of people each year and the impact of influenza on the global economy and in our everyday lives has been well documented. Influenza viruses not only infect humans but also are zoonotic pathogens that infect various avian and mammalian species, which serve as viral reservoirs. While there are several strains of influenza currently circulating in animal species, H2 influenza viruses have a unique history and are of particular concern. The 1957 'Asian Flu' pandemic was caused by H2N2 influenza viruses and circulated among humans from 1957 to 1968 before it was replaced by viruses of the H3N2 subtype. This review focuses on avian influenza viruses of the H2 subtype and the role these viruses play in human infections. H2 influenza viral infections in humans would present a unique challenge to medical and scientific researchers. Much of the world's population lacks any pre-existing immunity to the H2N2 viruses that circulated 50–60 years ago. If viruses of this subtype began circulating in the human population again, the majority of people alive today would have no immunity to H2 influenza viruses. Since H2N2 influenza viruses have effectively circulated in people in the past, there is a need for additional research to characterize currently circulating H2 influenza viruses. There is also a need to stockpile vaccines that are effective against both historical H2 laboratory isolates and H2 viruses currently circulating in birds to protect against a future pandemic.